Maternity leave versus early childcare – What are the long-term consequences for children? - Nabanita Datta Gupta (IZA World of Labor, 2018)
Most OECD countries spend substantially more on maternity leave schemes than on early childcare. However, given high tax burdens and rapidly aging populations, female labor force participation is critically needed. Moreover, it is important to know whether the main beneficiaries, the children themselves, reap more benefits from one or the other in the long term. The first cohorts exposed to the introduction or extension of maternity/paternity leave schemes and subsidized childcare programs have now completed education and entered the labor market, allowing an investigation of these programs' long-term economic effects.
Keywords: J13; 330; publicly subsidized childcare; maternity leave schemes; long-term outcomes